Endovascular mechanical thrombectomy for cerebral venous sinus thrombosis: a systematic review. (17th February 2017) - Ilyas, Adeel; Chen, Ching-Jen; Raper, Daniel M; Ding, Dale; Buell, Thomas; Mastorakos, Panogiotis; Liu, Kenneth C
Abstract : Background: Cerebral venous sinus thrombosis (CVST) is an uncommon form of stroke that, when severe, can be a therapeutic challenge. Endovascular mechanical thrombectomy (EMT) techniques have significantly evolved over the past decade, but data regarding the efficacy and safety of EMT for CVST are poorly defined. Objective: To summarize the large number of case series on this relatively rare condition and establish trends in the outcomes of EMT for CVST. Methods: A literature review was performed using PubMed and Medline to identify reports of three or more patients with CVST treated with EMT. Baseline and outcomes data, including radiographic resolution, neurological outcome, recurrence, and treatment-related complications, were extracted for analysis. Results: A total of 17 studies comprising 235 patients treated with EMT were included for analysis. Based on pooled data, 40.2% of patients presented with encephalopathy or coma. Concurrent endovascular thrombolysis was employed in 87.6% of patients. Complete radiographic resolution of CVST was achieved in 69.0% of patients. At follow-up (range 0.5–3.5 years), 34.7% of patients were neurologically intact and the mortality rate was 14.3%. CVST recurrence was evident in 1.2%. Worsening or new intracranial hemorrhage (ICH) occurred in 8.7% of cases. ORs of good outcome (modified Rankin Scale score 0–2) and development of ICH with sole EMT versus concurrent thrombolytic therapy were 1.51 (95% CI 0.29 to 8.15, p=0.61) and 1.15 (95% CI 0.12 to 10.80, p=0.90), respectively. Conclusions: EMT is an effective salvage therapy for refractory CVST, with a reasonable safety profile. Chemical thrombolysis, in conjunction with EMT, did not appear to result in additional harm or benefit. Further analysis is warranted to determine predictors of success after EMT for CVST.